2012
DOI: 10.1038/npp.2012.126
|View full text |Cite
|
Sign up to set email alerts
|

Regional Decoupling of N-acetyl-aspartate and Glutamate in Schizophrenia

Abstract: Proton magnetic resonance spectroscopy (¹H-MRS) allows the non-invasive measurement of several metabolites, including N-acetyl-aspartate (NAA), an amino acid exclusively synthesized in the mitochondria of neurons, and glutamate, an amino acid involved in excitatory neurotransmission and metabolism. In view of recent postmortem studies in schizophrenia (SZ) revealing mitochondrial abnormalities as well as perturbed expression of the enzymes regulating the glutamate-glutamine cycle, we hypothesized that a disrup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
60
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 53 publications
7
60
0
Order By: Relevance
“…[26][27][28][29][30] However, the quality of the spectral fits is not always clear in these reports (except for [27][28][29] ) and the samples were small (9 to 30 for the schizophrenia groups 6 ). More recent studies reported increases, [31][32][33][34][35] reductions 25,[36][37][38] and no differences 39 in Glx or glutamate. Two 33,34 of the 5 recent studies documenting elevations involved more ventral regions.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28][29][30] However, the quality of the spectral fits is not always clear in these reports (except for [27][28][29] ) and the samples were small (9 to 30 for the schizophrenia groups 6 ). More recent studies reported increases, [31][32][33][34][35] reductions 25,[36][37][38] and no differences 39 in Glx or glutamate. Two 33,34 of the 5 recent studies documenting elevations involved more ventral regions.…”
Section: Discussionmentioning
confidence: 99%
“…One metaanalysis found that glutamate is reduced and glutamine is increased in the ACC in patients with schizophrenia, and both decrease more markedly with age in patients [38]. A more recent meta-analysis found higher medial-frontal Glx (glutamate + glutamine) levels in high-risk subjects [39]. Three recent studies used ultra-high field strength (7T) MRS, as its greater spectral resolution and signal-to-noise ratio help to distinguish between these two metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Since previous studies have reported correlations between glutamate and NAA in certain brain areas (Colla et al, 2009;Waddell et al, 2011;Kraguljac et al, 2012) and in due consideration that glutamate and NAA are linked through the Krebs cycle (tricarboxylic acid cycle) (Moffett et al, 2007), the altered NAA concentrations in the present study are more comprehensible. Owing to this connectivity of the two compounds, some authors hypothesized that the abundant supply of NAA in neurons provides a reservoir for glutamate (Clark et al, 2006).…”
Section: Discussionmentioning
confidence: 62%